Atmospheric driving mechanisms of flash floods in Portugal - Santos, Mónica (2017)
The present study aims to investigate how large-scale atmospheric circulation may influence flash floods in Portugal. For this purpose, weather types (WTs) in a northeastern North Atlantic sector are used and flash floods between 1950 and 2003 were identified in six hydrographic basins: three in the north of Portugal and another three in the south of Portugal. An adapted methodology for flash flood detection on daily discharges is applied. A total of 131 flash floods were detected: 35 in the northern basins and 96 in the southern basins.WTs are identified using the National Oceanic and Atmospheric Administration 20th Century Reanalysis V2. The sea level pressure composites for flash flood days by WT reveal the large-scale atmospheric patterns underlying their occurrence. The results show that the cyclonic (C) type was strongly associated with flash flood days in the northern basins. The C type pattern features deep low pressure systems north of Iberia, much stronger than average for this WT. For the southern basins, the C type still shows the highest relevance for flood occurrence, but to a lesser extent, since the easterly wind (E) and dual anticyclonic (AA) types also acquire some importance. The flash flood-inducing AA-type events are characterized by atypical largely zonal troughs extending towards Portugal. The flash flood-inducing E type events hint at the occurrence of anomalously strong cut-off low pressure systems over southern Portugal. Although the significance of these systems to precipitation in Portugal was addressed in previous studies, a systematized assessment of their role on flash flood occurrences is herein provided for the first time. The presented flash flood detection methodology can be applied to other regions where hourly flow discharge data are not available, thus being an alternative to the more conventional detection algorithms.